2002
DOI: 10.1523/jneurosci.22-15-06321.2002
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Induces Dopamine and Glutamate Release in the Shell of the Nucleus Accumbens

Abstract: An increase in the extracellular concentration of dopamine in the nucleus accumbens (NAc) is believed to be one of the main mechanisms involved in the rewarding and motor-activating properties of psychostimulants such as amphetamines and cocaine. Using in vivo microdialysis in freely moving rats, we demonstrate that systemic administration of behaviorally relevant doses of caffeine can preferentially increase extracellular levels of dopamine and glutamate in the shell of the NAc. These effects could be reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
198
3
18

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(234 citation statements)
references
References 22 publications
15
198
3
18
Order By: Relevance
“…This hypothesis might seem at odds with the results of several reports that indicate that caffeine can reinstate or prevent the extinction of cocaine-seeking behaviour (Worley et al, 1994;Schenk et al, 1996;Self et al, 1996;Kuzmin et al, 1999;Green and Schenk, 2002;Weerts and Griffiths, 2003). However, these effects of caffeine appear to be due to A 1 rather than A 2A receptor blockade (Kuzmin et al, 1999;Green and Schenk, 2002, Solinas et al, 2002, 2005Karcz-Kubicha et al, 2003;Quarta et al, 2004Quarta et al, 2005Antoniou et al, 2005). Thus, caffeine and selective A 1 receptor antagonists have many behavioral, subjective and biochemical similarities to other psychostimulants, including their ability to induce dopamine release in the nucleus accumbens (Solinas et al, 2002(Solinas et al, , 2005Karcz-Kubicha et al, 2003;Quarta et al, 2004aQuarta et al, , 2004bAntoniou et al, 2005).…”
Section: Adenosine a 2a Receptors In The Ventral Striatum And Drug-sementioning
confidence: 95%
See 2 more Smart Citations
“…This hypothesis might seem at odds with the results of several reports that indicate that caffeine can reinstate or prevent the extinction of cocaine-seeking behaviour (Worley et al, 1994;Schenk et al, 1996;Self et al, 1996;Kuzmin et al, 1999;Green and Schenk, 2002;Weerts and Griffiths, 2003). However, these effects of caffeine appear to be due to A 1 rather than A 2A receptor blockade (Kuzmin et al, 1999;Green and Schenk, 2002, Solinas et al, 2002, 2005Karcz-Kubicha et al, 2003;Quarta et al, 2004Quarta et al, 2005Antoniou et al, 2005). Thus, caffeine and selective A 1 receptor antagonists have many behavioral, subjective and biochemical similarities to other psychostimulants, including their ability to induce dopamine release in the nucleus accumbens (Solinas et al, 2002(Solinas et al, , 2005Karcz-Kubicha et al, 2003;Quarta et al, 2004aQuarta et al, , 2004bAntoniou et al, 2005).…”
Section: Adenosine a 2a Receptors In The Ventral Striatum And Drug-sementioning
confidence: 95%
“…However, these effects of caffeine appear to be due to A 1 rather than A 2A receptor blockade (Kuzmin et al, 1999;Green and Schenk, 2002, Solinas et al, 2002, 2005Karcz-Kubicha et al, 2003;Quarta et al, 2004Quarta et al, 2005Antoniou et al, 2005). Thus, caffeine and selective A 1 receptor antagonists have many behavioral, subjective and biochemical similarities to other psychostimulants, including their ability to induce dopamine release in the nucleus accumbens (Solinas et al, 2002(Solinas et al, , 2005Karcz-Kubicha et al, 2003;Quarta et al, 2004aQuarta et al, , 2004bAntoniou et al, 2005). Nevertheless, we should distinguish between acute and chronic caffeine treatment.…”
Section: Adenosine a 2a Receptors In The Ventral Striatum And Drug-sementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, microdialysis studies showed that dopamine levels rise in the brains of rats after an acute caffeine administration, suggesting a direct effect of the ergogenic compound on dopamine synthesis. This effect was also dependent on the dose of caffeine used, and therefore on the elicited levels of caffeine in the brain tissue [31]. However, these data were contradicted by a report performed on humans, demonstrating that caffeine increases striatal dopamine D2/ D3 receptor availability and not dopamine levels at doses that are relevant to human consumption [25].…”
mentioning
confidence: 90%
“…Blockade of adenosine receptors within the striatal regions amplifies dopamine neurotransmission (Fuxe et al, 2007). Caffeine increases extracellular dopamine in the striatum and prefrontal cortex (Borycz et al, 2007;De Luca et al, 2007;Solinas et al, 2002) and dopamine receptor antagonism blocks caffeine-induced locomotor activity (Garrett and Holtzman, 1994;Nehlig et al, 1994). Thus, caffeine's actions in the brain are likely due to both adenosine receptor antagonism as well as amplification of dopamine neurotransmission.…”
Section: Introductionmentioning
confidence: 99%